Perekisnoe okislenie lipidov i "tribulinovaya" aktivnost' mochi kak pokazateli neinvazivnogo kontrolya stress-ustoichivosti gandbolistov v period sorevnovanii - Dyatlov, D. A.; Lvovskaya, E. I.; Voltchegorskii, I. A.; Pushkarev, E. D.; Yanchenko, N. A. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The authors of this article are in searching of new uninvasive methods of athletes' psychological stability evaluation. It is accepted, that psychological stability is most important during emulative periods. The aim of this study was to research the elite handball players' stress-resistance before and after a lap. By the authors' plan, that parameter should be studied by defining of lepids peroxide oxidation in exhaled air condensate and by "tribulative" urine activity. In conclusions of the article, the authors noted a necessity of lepoperoxidation processes and "tribulative" urine activity researching for athletes' stress-resistance evaluation and psychological states prediction.